Unlocking Potential with Entrepreneurship Training for Vocational High School Students - Tarso; Suryatama, Handika; Saputra, Surya Adi; Hanama, Akhmad; Siswanto, Deny Hadi (The Indonesian Institute of Science and Technology Research, 2024)
This training was specifically organized for 50 students from Muhammadiyah Vocational High School in Mlati, located in Sleman Regency. This activity aims to provide the necessary knowledge and skills in entrepreneurship, utilizing diverse teaching methods such as lectures, demonstrations, and classroom discussions. Through this approach, students are expected to gain a comprehensive understanding of the fundamental concepts of entrepreneurship. The training aims to foster a strong entrepreneurial spirit among the students so that after completing their education, they will not only focus on seeking employment but also be motivated to create job opportunities for themselves and others. With the rise of new entrepreneurs, it is hoped that this initiative will contribute to the government’s efforts in reducing unemployment rates and improving the overall welfare of society. This training serves as an essential first step in shaping a self-reliant and competitive generation in addressing the challenges of an increasingly demanding job market.